Aktualisasi Hadis Terhadap Krisis Akhlak Peserta Didik - Sari, Dwi Wulan (Al-Bayan: Jurnal Ilmu al-Qur'an dan Hadist, 2023)
Moral values are so important to be instilled for students from an early age in order to create a good life and be able to uphold the religious values and culture of the nation's ancestors. Lack of awareness of the central position of the learner so that there is a disregard for morals and their characteristics. Moral characteristics are a characteristic that must be possessed by students in order to create harmony between the educational part and the expected direction. This study aims to provide a description of the actualization of hadith to the moral crisis of learners. The research method in this writing uses qualitative with the type of literature study research. The results showed that the actualization of morals that are in accordance with the hadith and must be owned by students include intention, patience, sincerity, honesty, tawadhu and tawakal.